Prescription pattern of drugs in ENT outpatient department of tertiary care teaching hospital - Joshi, Usha; Banjara, Hansa; Hishikar, Rajesh; Chandrakar, Ravindra (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Diseases of the ear, nose and throat (ENT) are common among general population affecting all age groups and accounts for most of the drugs prescribed and used. The aim of the study is to assess the prescription pattern of drugs in ENT outpatient department in a tertiary care teaching hospital. Methods: A prospective observational study was conducted from December 2017 to May 2018 in the ENT OPD (Outpatient department) at Pt. J.N.M. Medical College and associated Dr. B.R. Ambedkar Memorial Hospital, Raipur. Data were collected in a proforma and evaluated. Results: A total of 313 prescriptions were analysed. Most of the patients (40.89%) belonged to 13 - 35 years age group.185 patients (59.10%) were male and 128 patients were females (40.90%). A total of 1003 drugs were prescribed. The average number of drugs per prescription was 3.2. Most common class of drugs prescribed was antimicrobials (24.42%), followed by H1 antihistaminics (18.84%), antiulcer drugs (15.55%) and nonsteroidal anti-inflammatory (NSAIDs) drugs (14.35%). The average number of antimicrobials per prescription was 0.78. One or two antimicrobials were prescribed in 202 prescriptions (64.53%). The most common prescribed antimicrobial was of Penicillin group (64.89%) followed by Fluoroquinolone (25.71%). The most common prescribed route of drug administration was oral route (81.35%). The most common prescribed dosage form was tablets (74.87%). FDC constituted 24.62% of prescribed drugs. Conclusions: The study revealed that the most common class of drug prescribed was antimicrobials followed by H1 antihistaminics, antiulcer drugs and NSAIDS.